The Oxford handbook of credit derivatives - Lipton, Alexander; Rennie, Andrew, 1968- (Oxford : Oxford University Press, 2011)
This handbook provides a timely discussion of the mathematical modelling that underpins both credit derivatives and securitisation. It covers statistical analysis and techniques modelling of default of both single and multiple entities counterparty risk, Gaussian and non-Gaussian modelling, and securitisation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Credit derivatives -- Mathematical models